Oxford American writer's thesaurus - Lindberg, Christine A., 1954- (New York : Oxford University Press, 2008)
"Written by writers for writers, this innovative thesaurus truly advances the time-honored word source. Some 25,000 word meanings and connotations are elucidated by means of more than 300,000 synonyms, 10,000 antonymns, 250 word notes written by noted authors, and generous listings of example sentences. Many special features, such as usage notes, word spectrums, and a language guide, further clarify a word's many nuances and assist the user in finding just the right expression. For all readers, wordsmiths, scribblers, and hacks, Oxford's new thesaurus should be on every library's reference shelf."--"Reference that rocks," American Libraries, May 2005.
Oxford Dictionaries Staff vi --Preface vii --Foreword viii-- Introduction xi --Guide to the Thesaurus xviii -- Features of the Text xviii-- Labels xix -- Featured Notes xx -- Notes by Contributing Authors xxi -- Word Notes xxii -- Usage Notes xxv-- Word Spectrums xxvii -- Oxford American Writer's Thesaurus 1 -- Wordfinder center section -- Contents and Index 1 --Thematic Lists 3 --Archaic Words 38 -- Literary Words 41-- Language Guide back section --Contents 1003 -- 1 Grammar 1005-- 2 Spelling 1032 -- 3 Capitalization 1039 -- 4 Punctuation 1047
Keywords: English language -- Synonyms and antonyms; English language -- Synonyms and antonyms